2023
DOI: 10.3390/dj11050119
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude towards Probiotics among Dental Students and Teachers: A Cross-Sectional Survey

Abstract: This cross-sectional survey assessed the knowledge of and the attitude towards probiotics of dental students and academics at Sechenov University, Moscow, Russia. Our questionnaire consisted of 15 questions divided into 3 sections: respondents’ sociodemographic data, knowledge on probiotics, and attitude towards probiotics. The data were analyzed using the Mann–Whitney U test, Fisher’s exact test, and Spearman’s rank correlation coefficient. Out of the 658 questionnaires distributed, a total of 239 questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Still, healthcare professionals may be reluctant to recommend probiotics to patients due to a paucity of the peer-reviewed literature on the topic and the absence of accepted evidence-based recommendations [ 56 , 57 ]. A systematic review by Ausenda et al concluded that more research on the topic was needed, as significant heterogeneity of the existing studies did not allow researchers to make firm conclusions and develop clinical recommendations regarding probiotics use in the treatment of periodontal diseases [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Still, healthcare professionals may be reluctant to recommend probiotics to patients due to a paucity of the peer-reviewed literature on the topic and the absence of accepted evidence-based recommendations [ 56 , 57 ]. A systematic review by Ausenda et al concluded that more research on the topic was needed, as significant heterogeneity of the existing studies did not allow researchers to make firm conclusions and develop clinical recommendations regarding probiotics use in the treatment of periodontal diseases [ 58 ].…”
Section: Introductionmentioning
confidence: 99%